Histopathology of Cysticercu sfasciolaris Batsch, 1786 (Cyclophyllidae: Taeniidae) extrinsic parasite of liver in infected rat (Rattus rattus) from Hyderabad, Sindh, Pakistan ... : علم التشريح المرضي لـ Cysticercu sfasciolaris Batsch، 1786 (Cyclophyllidae: Taeniidae) الطفيليات الخارجية للكبد في الفئران المصابة (Rattus rattus) من حيدر أباد، السند، باكستان ... - Farheen Shaikh (OpenAlex, 2023)
The aim of study was to examine pathology of tissues caused by Cysticercus fasciolaris (Cyclophyllidae: Taeniidae) a larval stage of a helminth parasite Taenia taeniformis in the infected liver of rats Rattus rattus.The study was carried out at the advance laboratory of Parasitology of the Department of Zoology, University of Sindh Jamshoro during the year from August 2018 to November 2019.A total of 08 brown rats Rattus rattus were entrapped from various localities of Hyderabad and were brought to the laboratory for examination of their helminthes parasites.A total of 08 rats were dissected and only 05 were found infected with Cysticercus fasciolaris on liver in the form of cysts.The samples of tissues from infected parts of the liver were obtained and fixed in bouin's solution.The series of sections were made by microtome technique and were finally mounted in Canada balsam.In the histopathological findings, the infected liver of rats revealed presence of mononuclear cells such as lymphocytes, macrophages, ... : كان الهدف من الدراسة هو فحص أمراض الأنسجة التي تسببها Cysticercus fasciolaris (Cyclophyllidae: Taeniidae) وهي مرحلة اليرقات من طفيلي الديدان الطفيلية Taenia teniformis في الكبد المصاب للفئران Rattus rattus. أجريت الدراسة في المختبر المتقدم لعلم الطفيليات في قسم علم الحيوان، جامعة السند جامشورو خلال العام من أغسطس 2018 إلى نوفمبر 2019. تم اصطياد ما مجموعه 08 فئران بنية اللون راتوس راتوس من مواقع مختلفة من حيدر أباد وتم إحضارها إلى المختبر لفحص طفيليات الديدان الطفيلية. تم تشريح ما مجموعه 08 فئران وتم العثور على 05 فئران فقط مصابة بالتهاب اللفافة الكيسية المذنبة على الكبد في شكل أكياس. تم الحصول على عينات من الأنسجة من الأجزاء المصابة من الكبد وتثبيتها في محلول بوين. تم إجراء سلسلة من الأقسام بتقنية الميكروتوم وتم تركيبها أخيرًا في بلسم كندا. في النتائج النسيجية المرضية، كشف كبد الفئران المصاب عن وجود خلايا أحادية النواة مثل الخلايا الليمفاوية والبلاعم الكبيرة والخلايا اليوزينية وخلايا البلازما والتسلل الخلوي متعدد النوى في المنطقة الميتة، الدهنية تفكك وتطور مناطق التخثر ونخر الخلايا الكبدية. كان الكبد المصاب ...